Telemedicine use in current urologic oncology clinical practice - Paesano, Nahuel; Carrion, Diego M.; Autrán Gomez, Ana María (Frontiers in Surgery, 2022)
In the last fifteen years, important investments and technological advances have been made in telehealth systems, and urological practice, together with other specialties, has been a pioneer in the successful use of this medical care modality. Nowadays, due to the current COVID-19, telemedicine has been rapidly adopted by the urologic community worldwide. A review of the most relevant and updated articles on telemedicine and telehealth in urology has been carried out. The current literature indicates that telemedicine in urology has proven to be useful in a variety of clinical scenarios within urological practice, from benign disease to advance cancers, and from the initial diagnosis to follow-up. This is due to the positive impact on medical consultation times, lower patient mobility costs, less work absenteeism, and greater protection for both the patient and the doctor. The main limitations for the use of telemedicine lie in the impossibility of a correct physical examination, essential in certain situations, as well as the lack of accessibility to technology in unfavorable populations and in older adult patients who did not adapt to the use of technology.